A Triple Framework to Understand the Role of Cultural Heritage: Heritage, Identity and Literature - Dekhir, Faiza (المركز الجامعي أمين العقال الحاج موسى أق أخموك بتامنغست, 2019)
يبدو اليوم مشوقا في الدراسات الاجتماعية والثقافية مناقشة الموضوعات المتعلقة بالتراث الثقافي. إن أحد أسباب ذلك رد فعل لسرع ظاهرة العولمة في العقود الأخيرة، حيث تتعرض ثقافة حياتنا" لخطر الاختفاء والاستعاضة عن ثقافاتهم "العالمية". يدور هذا العمل حول فائدة التراث في التعبير عن الهوية الوطنية للمرء من خلال الأعمال الأدبية لبعض المؤلفين ككاتب ياسين مثلا. قد يبدو من المناسب، إذن، اعتبار الهوية الوطنية أحد مكونات التراث من خلال المشاركة والتعرض للمصنفات الأدبية. وبالتالي، من أجل فهم واضح للعلاقة بين التراث الثقافي والهوية والأعمال الأدبية، من المهم أن نمر بتعريفاتهم.
It is interesting today in social and cultural studies to debate topics relating to cultural heritage. One reason for that could plausibly be a reaction to the hastening of globalization nowadays, in which the ‘our’ culture is at risk of being vanished and substituted for globally ‘their’ cultures. This work then highlights the usefulness of heritage in expressing one’s national identity through literary works. It is appropriate then, to view national identity as one component of heritage through engagement and exposure to literary works by different authors like Kateb Yacine for instance. Thus, in order to clearly understand the association between cultural heritage, identity and literary works, it is important to go through their definitions.
Keywords: التراث الثقافي -- الهوية الوطنية -- الأدب العربي